2013
DOI: 10.1183/09031936.00024313
|View full text |Cite
|
Sign up to set email alerts
|

Differences in plasma and sputum biomarkers between COPD and COPD–asthma overlap

Abstract: The pathophysiological features of chronic obstructive pulmonary disease (COPD)-asthma overlap are poorly understood and there has been no study of plasma or sputum biomarkers in overlap patients. In order to clarify the similarity and differences between overlap and COPD or asthma, we have investigated four potential biomarkers of COPD: surfactant protein A (SP-A), soluble receptor for advanced glycation end-products (sRAGE), myeloperoxidase (MPO) and neutrophil gelatinase-associated lipocalin (NGAL). SP-A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 42 publications
6
105
1
1
Order By: Relevance
“…Iwamoto showed increased sputum eosinophilia in patients with asthma and ACOS compared with healthy smokers and those with COPD [Iwamoto et al 2014]. However, patients with overlap syndrome and COPD had more sputum neutrophilia compared with those with asthma and healthy controls.…”
Section: Airway Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwamoto showed increased sputum eosinophilia in patients with asthma and ACOS compared with healthy smokers and those with COPD [Iwamoto et al 2014]. However, patients with overlap syndrome and COPD had more sputum neutrophilia compared with those with asthma and healthy controls.…”
Section: Airway Inflammationmentioning
confidence: 99%
“…Lower NOx might indicate a decrease in oxidant activity compared with COPD alone. Iwamoto and colleagues investigated four potential biomarkers in COPD, asthma and ACOS [Iwamoto et al 2014]. Compared with asthma, sputum myeloperoxidases and plasma surfactant protein A were significantly elevated in ACOS and COPD and soluble receptor for advanced glycation end products was decreased in ACOS and COPD.…”
Section: Biomarkersmentioning
confidence: 99%
“…The involvement of pulmonary surfactant in the pathophysiology of asthma has been suggested [1][2][3][4]. An interesting working hypothesis is that the surface tension of the peripheral airways is altered in asthma, because the inflammatory process affects the structure and function of surfactant, leading to excessive airway narrowing and features of air trapping.…”
Section: To the Editormentioning
confidence: 99%
“…IWAMOTO et al [18] reported elevated sputum lipocalin, a neutrophil marker, as differentiating COPD and ACOS. In contrast, BAFADHEL et al [19] found that the mediator profile reflected the pattern of granulocytic inflammation, which is not specific for a diagnosis of asthma or COPD.…”
Section: The Genetics Of Acosmentioning
confidence: 99%